A language extension to support persistent objects in C++ - Reyes, Lolita E. Villanueva (Animo Repository, 2002)
Traditional programming languages such as C++ only provides operations for manipulating and storing transient data. These are data dependent on the activation of the program. Explicit file manipulation is needed in order to support persistent data. PEPC++, peristent programming in C++, deals with extending the C++ programming language to support persistence of objects. The paper also discusses implicit handling of the retrieval of previously stored state of the object, and the storage of the current state of the object. The paper presents the two new contructs, persist and get, and the necessary operations provided for the manipulation of persistent objects. The persistent keyword specifies that an object is persistent while the get construct allows a PEPC++ program to use previously defined persistent objects in other PEPC++ programs. The two operations provided for manipulating persistent objects are the PEPC_load() and PEPC_save() methods. The PEPC_load() method retrieves the previously stored state of the persistent objects On the other hand , the PEPC_saved() method stores the current state of the persistent object.